ANALYSIS OF COMMUNITY HEALTH CENTER MANAGEMENT IN IMPROVING SERVICE QUALITY AT DULUKAPA HEALTH CENTER, NORTH GORONTALO REGENCY: Ely Ibrahim - Sri Nangsi Ladici; Ely Ibrahim; Zuchri Abdusamad (Jurnal Ilmu Manajemen dan Bisnis, 2023)
The research objective is (1) Knowing how the management of the Puskesmas in improving the quality of service at the Dulukapa Puskesmas, North Gorontalo Regency. (2) To find out the factors that determine the management of the Puskesmas in improving the quality of service at the DulukapaPuskesmas, North Gorontalo Regency. The type of research used is a qualitative approach with a descriptive research design. The social situation used in this study is place, person, activity.In this study there are types and sources of data, namely primary data sources and secondary data sources. Data collection techniques used in this research are observation, interviews, and documents.Data analysis techniques in this study are data collection, data reduction, and data display, conclusion or verification. Test the validity of the data is done by testing the credibility. The results of the study are (1) Concerning the management of the Puskesmas in improving the quality of service at the Dulukapa Puskesmas, North Gorontalo Regency, it can be seen from the activities of planning, movement and implementation, supervision, control and performance evaluation that have not been carried out optimally, because it is not entirely rare that is contained in the implementation of management that is carried out consistently and continuously to realize quality Puskesmas governance. This is evidenced by the "Basic" accreditation status achieved by the Dulukapa Health Center in 2017. (2) The factors that determine the management of the Health Center in improving the quality of service at the Dulukapa Health Center, North Gorontalo Regency, are the absence of adequate human resources, Standard Operating Procedures (SOP) have not been fully implemented, and the facilities and infrastructure at the Puskesmas are inadequate and function optimally to support health services at the Puskesmas.